Bony findings detected by MRI may reflect the pathophysiology of osteoarthritis with thumb carpometacarpal joint pain. (18th November 2015) - Komatsu, Masatoshi; Kamimura, Mikio; Nakamura, Yukio; Mukaiyama, Keijiro; Ikegami, Shota; Hayashi, Masanori; Uchiyama, Shigeharu; Kato, Hiroyuki
Abstract: Background: Osteoarthritis (OA) is the most common skeletal disease worldwide. Although thumb carpametacarpal joint (CMJ) OA is also frequently encountered, the etiologies remain largely unknown. Method: We analyzed 20 patients who had thumb CMJ OA with accompanying joint pain and categorized a total of 37 thumbs according to the Eaton and Littler staging system. Results: In patients with advanced OA, bone alterations as detected by magnetic resonance imaging (MRI) were observed in almost all of the painful joints. The frequency of bone alterations in the thumb CMJ increased with OA severity. In contrast, MRI revealed no bone alterations in thumbs with no pain and less pain in bilateral thumb basal pain, even in radiographically advanced OA. Conclusions: While the incidence of bone cysts in the CMJ was higher with OA staging, OA severity had no apparent correlation with pain. Thus, it is possible that the cause of thumb CMJ pain in advanced OA is bone alterations.